THE COMPARATIVE ANALYSIS OF PLAN AND ACTUALFUEL RATIO ON THE LOADING TOOLS OF KOBELCO SK 520, SK 330 EXCAVATORS AND HAULING TOOL OF HINO FM260 JD DUMP TRUCK : ON THE ACTIVITIES OF OVERBURDEN REMOVAL AND COAL GETTING AT PT TRUBA BARA BANYU ENIM, MUARA ENIM REGENCY, SOUTH SUMATERA - Roby Cahyadi,; Tiara Anggraini,; Isdaryanto Iskandar, (Jurnal Cakrawala Ilmiah, 2022)
One of the biggest needs in mining activities is mechanical equipment to achieve production target which needs fuel. A mechanical tool is declared successful if it is able to meet the production target by using a minimum of fuel consumption. The excessive use of fuel will affect the company's profits. The ratio between total fuel consumption and total production is called the fuel ratio. A company is successful or gains profit if the plan fuel ratio is higher that the actual fuel ratio. The aim of this research was to analyze the comparison between plan and actual fuel ratio on Kobelco SK 520, Kobelco SK 330 excavators and Hino FM 260 JD Dump Truck. This analysis process was conducted by knowing the production target and realization of the overburden and coal getting production target. In March 2022, the production of SK 520 was 43,147.97 BCWmonth, DT 8-193 10,328.07 BCM/month, SK 330 was 41,981.76 tonnes/month, DT 8-138was 8,169.43 tonnes/month. In April 2022, the production of SK 520 was 50,188.03 BCM/month, DT 8-193 was 8,750.25 BCWmonth, SK 330 was 38,555.66 tonnes/month, DT 8-138 was 8,432.83 tonnes/month. The fuel ratio in March were SK 520 of 0.19 litre/BCM, DT 8-193 of 0.27 litrefBCM, SK 330 of 0.17 litre/ton and DT 8-138 of 0.23 litre/ton. The fuel ratio in April 2022 were SK 520 ofO. 19 litre/BCM, DT 8-193 ofO.29 litre/BCM, SK 330 of0.18 liter/ton, and DT 8-138 of 0.21 litre/ton. The loss of fuel ratio in March 2022 on the overburden removal was SK 520 of Rp 22,652,684 and DT 8-193 of Rp the coal getting activity on SK 330 was Rp 36,734,040 and DT 8-138 of Rp In April 2022, the loss on the overburden removal on SK 520 was Rp 35,733,877.36 and on DT 8-193 was Rp 7,787,723, and the coal getting on SK 330 was Rp 27,451,630 and DT 8-138 was Rp 6,004,175.